Modelling and control of constrained robot systems with uncertainties in the constraint functions - Ho, Yeong Khing. (2010)
Constrained robot motion control is a special class of robot control where both the trajec-tory and the contact force have to be considered. For effective control of this class of robot systems, we need to consider the robot dynamics and the constraining environments as inte-grated constrained robot dynamics. In this thesis, a model for the constrained robot dynam-ics, incorporating constraint uncertainties is developed. The algebraic constraint functions represent the rigid constraining surfaces. The uncertain terms in the constraint functions explicitly account for the constraint uncertainties. The uncertainties reflect the inaccuracy in the descriptions of the constraining surfaces. It is shown in the analysis that the constraint uncertainties influence the robot dynamics, giving rise to the need to take into considerations these uncertainties in controlling the constrained robots. The modelling is extended to deal with stiff environments where deformations of surfaces occur when a robot interacts with the environments. The surface deformations are treated as uncertainties in the constraint functions describing the nominal surfaces.